2012
DOI: 10.4236/eng.2012.411096
|View full text |Cite
|
Sign up to set email alerts
|

Application of Heterogenous Catalysis with TiO2 Photo Irradiated by Sunlight and Latter Activated Sludge System for the Reduction of Vinasse Organic Load

Abstract: Vinasse is the main residue generated during alcohol, sugar and blue rum production by fermentation process. This residue is effluent that could cause serious environmental pollution due to high organic load when is not treated adequately. The aim of this work consists of evaluating the efficiency and application of heterogeneous photocatalysis with TiO 2 , followed by a biological treatment (activated sludge system) to reduce organic load in the referred effluent. Complete factorial designs indicated the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…A new experiment was conducted with the optimized parameters from this study and the ones found in [10], that is, pH of 8.0, ZnO coating thickness of 100 m, reaction time of 3 h, effluent concentration in natura, average radiation of 584.0 W/cm 2 , reaction temperature of 31 ∘ C, and average evaporation rate of 0.17 L/h. The TOC percentage removal was of 32% as obtained by [8,12,13], though the authors employed TiO 2 with lower organic load.…”
Section: Optimization Of the Photocatalytic Process By Using The Surfmentioning
confidence: 89%
See 2 more Smart Citations
“…A new experiment was conducted with the optimized parameters from this study and the ones found in [10], that is, pH of 8.0, ZnO coating thickness of 100 m, reaction time of 3 h, effluent concentration in natura, average radiation of 584.0 W/cm 2 , reaction temperature of 31 ∘ C, and average evaporation rate of 0.17 L/h. The TOC percentage removal was of 32% as obtained by [8,12,13], though the authors employed TiO 2 with lower organic load.…”
Section: Optimization Of the Photocatalytic Process By Using The Surfmentioning
confidence: 89%
“…The immobilization of ZnO particles was carried out by the application of a coating containing the photocatalyst [8] by DuPont do Brasil S.A., in Guarulhos, Sao Paulo. Two identical 800 × 250 mm stainless steel plates with an area of 200 cm 2 were used each with a different thickness (50 and 100 m).…”
Section: Preparation Of the Zno Coating And Experiments Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto menor a quantidade de pigmento, maior a espessura requerida para se ter a massa desejada (no caso, 0,025 ou 0,05 g cm -²) e quanto maior a quantidade de pigmento, menor a espessura. Desta forma, foram realizados cálculos para a determinação da espessura ideal do filme, formado com 18 % de titânio e o teor de pigmento desejado dentro de uma área de 1 cm² (Carrocci et al, 2012). Conforme análises realizadas na própria DuPont, o filme da placa utilizada contendo anatase apresentou espessura variando de 55 a 65 µm.…”
Section: Revestimento Da Placa Metálica Do Reator Com Tiounclassified
“…Agro-food industrial processes lead to large amounts of by-product as vinasse (Carrocci et al 2012;Christofoletti et al 2013). Vinasse is generally used as an additive for animal feed because it contains a large fraction of organics (proteins, pectins, polyphenols, and colored compounds) and as a fertilizer because its mineral composition is rich in NPK elements.…”
Section: Introductionmentioning
confidence: 99%